P-300 Evaluation of CYP19A1 gene expression in luteinized granulosa cells of women affected by endometriosis undergoing assisted reproductive technology (ART) treatments. (30th June 2022) - Giacomini, E; Minetto, S; Kleeman, F; Pagliardini, L; Pinna, M; Papaleo, E; Candiani, M; Somigliana, E; Viganò, P
Abstract: Study question: Does endometriosis affect the expression of the aromatase gene CYP19A1 in the cumulus oophorous (COCs) and mural lutein-granulosa cells (GCs) influencing ART procedures? Summary answer: Endometriosis does not impair CYP19A1 gene expression. However, the correlation between the aromatase expression and the number of oocytes retrieved is lost in endometriosis patients. What is known already: Endometriosis-related infertility could be associated with a dysregulation of oocytes development. Indeed, endometriosis seems to have a negative effect on the intrafollicular environment, hindering oocyte maturation. A dysregulated synthesis of steroid hormones by GCs in the ovaries of affected women may be at the basis of an inadequate folliculogenesis. In line, some studies have investigated the expression levels of aromatase p450 ( CYP19A1 ) -the key enzyme involved in 17β-estradiol (E2) synthesis - in GCs and COCs collected from endometriosis women, reporting controversial results. Study design, size, duration: In order to identify novel prognostic factors of ART outcomes in affected women, we set the evaluation of CYP19A1 expression in GCs samples isolated from endometriosis patients undergoing ART in comparison to control women. In a subgroup of patients, COCs were also collected. CYP19A1, StAR and 3βHSD gene expression was evaluated in both cell types. Finally, we evaluated the association between the expression of the analyzed genes and E2 levels with the clinical ART outcomes Participants/materials, setting, methods: GCs were isolated from follicular fluids(FF) of n = 68 women with stage III-IV endometriosis and of n = 69 control patients. CYP19A1 gene expression was quantified by qPCR. 17β-estradiol levels in FF were assessed using an ELISA kit. In addition to CYP19A1 gene expression, mRNA levels of StAR and 3βHSD both in GCs and COCs (n = 20 endometriosis;n=21 controls) were evaluated in both cell types using qPCR. Differences between the two patients' groups were estimated using linear regression models. Main results and the role of chance: qPCR results showed no differences in mRNA expression of CYP19A1, StAR and 3βHSD in both GCs and COCs between the two groups of ART patients. These results were supported by the presence of the same concentration of E2 in the FF of controls (median: 877.7 ng/mL) and endometriosis patients (median: 878.3 ng/mL) (p-value=0.87). Linear regression model including as input variables gene expression values and ART outcomes showed that the blastulation rate was the only ART outcome associated with the expression levels of CYP19A1  (p-value=0.043, 95% CI: 0.001-0.061). In particular, a decrease of aromatase levels was associated with an increase in blastulation rate. After stratification of the population based on the presence of the disease, it emerged that, in the control group, the CYP19A1 expression correlated with the number of oocytes retrieved [β:-1.214;95%CI: -2.085 - (-0.343); p-value=0.007], while in the group of patients with endometriosis this association was no more present [β:-0.003;95%CI:-0.468 - 0.461; p-value=0.988)]. These results do not support data from the literature indicating that aromatase expression is reduced in GCs of affected women, but they highlight a potential disease-related mechanism affecting the ovulation process in these women Limitations, reasons for caution: These findings need to be validated in a different cohort of samples. An RNA-seq approach is needed in order to validate our results and to obtain the overall transcriptome profiles of GCs and COCs in endometriosis patients. Wider implications of the findings: Our data do not confirm previous evidence supporting a reduced expression/activity of aromatase in GCs in endometriosis. However, they suggest that aromatase may have a complex and sophisticated regulation of its expression in this cell type, which is not maintained in presence of endometriosis. Trial registration number: not applicable